ENGL 100 introduction to literature (Boston Pearson, 2016)
Pedagogically current and uncommon in its breadth of representation, The Broadview introduction to literature invites students into the world of literary study in a truly distinctive way.
Short fiction -- Drama -- Poetry -- Poetry in translation -- Literary non-fiction.
Includes indexes.
The section Poetry includes poems in Spanish, German, French, Hebrew and Tigrinya followed by their English translations.
Keywords: Literature -- Collections